EDUCATIONAL POTENTIAL OF THE “SOCIAL ACCELERATOR” TECHNOLOGY: DEVELOPING SOCIAL – ENTREPRENEURIAL COMPETENCE OF STUDENTS AT CLASSICAL UNIVERSITIES - E. G. Syryamkina; T. B. Rumyantseva; E. Yu. Liventsova (Obrazovanie i Nauka)
Introduction. Modern trends in the development of education and society as a whole not only strengthen the role of modern universities in transformation of the social sphere, but also require a new approach to developing skills and over-professional competencies of university students, especially students of social and humanitarian specialties, who will live in conditions of a new technological paradigm. In this connection, classical universities have a special role because social and cultural development of society is their original mission. Therefore, development of social and entrepreneurial competence of students is an urgent educational task of modern classical universities. Education of social entrepreneurs is one of the relevant educational tasks which solution enables to provide additional resources for growth of welfare of fellow citizens. The work of social entrepreneurs is directed to the creative solution of social problems of the region, the help to its residents and positive changes in local society.The aim of the article is to demonstrate the experience of approbation of the educational technology for developing social and entrepreneurial competence of students in a classical university.Methodology and research methods. The methodological basis of the work is based on system-activity and competence approaches. The authors have used such methods as analysis of scientific literature; analysis of documents; desktop research; interviewing and questioning of participants in the educational process; educational experiment; reflection and generalisation of practical experience of implementing a program of accelerating business projects in a classical university (case study).Results and scientific novelty. The new approach to the development of social and entrepreneurial competence of students is proposed by the authors; that approach is based on the introduction of “Social Accelerator” technology into educational practice of higher education institutions. The technology structure is described; as obligatory components, the structure includes: short-term (several months long) program of training of the beginning entrepreneurs; mentor maintenance of students’ start-ups promotion; creation of conditions to present students’ project products to the public. The summary of the “Social Accelerator” functioning cycle is given. The results of its approbation carried out from 2015 to 2017 on the platform of the Park of Social and Humanitarian Technologies of the Tomsk State University are presented. The analysis of students’ responses proved emergence of a sustained interest to social and reformative activity and desire to continue training in the chosen direction at city, regional, all-Russian and international schools and programs.Practical significance. The “Social Accelerator” technology proposed by the authors is the innovative effective instrument of generation of a new wave of entrepreneurs; the technology can be used for students’ education at classical universities. The technology allows to: timely distinguish the persons who are capable of business activity; make active their initiative; provide timely assistance in development of enterprise tendencies and obtaining necessary knowledge.